'É na terra e no mar que tá nossa subsistência': resistência caiçara na Baía dos Castelhanos, Ilhabela - Silva, Paula Affonso de Araujo (2022)
This dissertation's objective was to make an ethnography of the relationships established between the caiçara communities of Baía dos Castelhanos, in the archipelago municipality of Ilhabela, and the various constraints to their way of life. Since the second half of the 20th century, especially after the creation of Ilhabela's State Park (PEIb), a series of documents and regulations have crossed the lives and possibilities of maintaining the caiçaras on lands they have occupied for over 200 years. The legal restrictions subsequent to the Park's creation were simultaneous to the intensification of real estate speculation, land grabbing and tourism, which significantly altered the environment and the caiçara way of life. At sea, other difficulties are imposed on the caiçaras, namely: exploration technologies that allow trawlers to leave the sea clean, exploration platforms in ultra-deep waters, presence of large oil tankers and the Route 1 gas pipeline that skirts the archipelago and drives part of pre-salt production to the Treatment Unit on the continent. Fishing is one of the activities whose regulation demanded the composition of new strategies and rearrangements of traditional practices, becoming, from the caiçaras' perspective, the last element giving meaning to their collective existence. Following local terms and evaluations, the caiçara way of resistance is operationalized in two forms: on land, through the incorporation of the papers’ logic, and at sea, through fishing techniques.